(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
During the research on the documentary objects for the film The invisibles, held in March 2021, was raised a material overview of the reminiscences related to the climatic catastrophe that occurred in the Mountain region of Rio de Janeiro in 2011, that is the central theme of the film. The article brings reflections on the experiences lived in the creation process of the film’s dramaturgy, which specifically encompass categories of objects that are related to the Mountain catastrophe. The article is divided into sections that reflect the relevance of the study groups carried out with residents of the Mountain region and the relationship of objects and their memories.